Analisis Pencatatan Laporan Keuangan Pada Usaha Gigi-Net: Jasa Pelayanan Dan Percetakan - Dwi Puja Kristian (CV ODIS, 2022)
The purpose of this research is to find out how to record financial statements at the Gigi-Net business, located at Jalan Ruko Taman Dhika Cluster Bromo No. 10 Buduran Sidoarjo. The author collects some data, such as primary data and secondary data. The data collection method used by the author is to conduct direct interviews with the Owner, documentation and observation. In data analysis used by the author is the descriptive method. Based on the observations made by the author, it can be seen that the Gigi-Net business was built to be self-managed. From the results of interviews with the Owner in their operational activities, they do not apply the accounting system because the Owner does not understand accounting. Therefore, the Owner has switched to using his idea to continue to carry out his operational activities so that it continues. Thus, the author is interested in knowing what the recording of financial statements by Gigi-Net is like without using an accounting system, but in his own way made by the Owner in a simple and easy to understand way. However, Gigi-Net's business can continue to run and even progress and develop until now